2018
DOI: 10.7240/marufbd.395068
|View full text |Cite
|
Sign up to set email alerts
|

Transferability of Barley Retrotransposons (Sukkula and Nikita) to Investigate Genetic Structure of Pimpinella anisum L.

Abstract: Transferability of barley retrotransposons (Nikita and Sukkula) were examined in Pimpinella anisum L. seeds by using a retrotransposon-based molecular marker: IRAP (inter-retrotransposon amplified polymorphism). Furthermore, transposons' sequences identified in medically important plants were obtained form NCBI, and multiple alignment analyses were performed to investigate the evolutionary relationships. These two retrotransposons were identified in Pimpinella anisum L., showing homomorphic band profiles. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Marakli [66]. Interestingly, polymorphism rate of Nikita in this study was calculated as 0-60%, suggesting that Nikita IRAP primer may also be used in further characterization and diversity studies.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Marakli [66]. Interestingly, polymorphism rate of Nikita in this study was calculated as 0-60%, suggesting that Nikita IRAP primer may also be used in further characterization and diversity studies.…”
Section: Discussionmentioning
confidence: 58%
“…In our study, we observed 0-100% polymorphism rate, suggesting that Sukkula retrotransposon is favourable to perform Colchicum characterization and diversity studies. Marakli [66]. Interestingly, polymorphism rate of Nikita in this study was calculated as 0-60%, suggesting that Nikita IRAP primer may also be used in further characterization and diversity studies.…”
Section: Several Studies Have Been Performed For Genetic Characterizamentioning
confidence: 58%
“…In one of these studies, Nikita and Sukkula retrotransposons were studied in the aniseed. Polymorphism was not found in both retrotransposons but their presence in the aniseed genome was determined (Marakli 2018). In another study, these two retrotransposons were identi ed in two varieties of black pine (Pinus nigra var.…”
Section: Discussionmentioning
confidence: 99%